Small DNA-free liposomes stimulate transfection of streptomyces protoplasts. - Rodicio, M R (1982)
DNA of the bacteriophage phi C31 was rendered DNase resistant by entrapment in liposomes. Liposome-entrapped phi C31 DNA transfected Streptomyces protoplasts in the presence of 50% polyethylene glycol (PEG), providing a potential alternative route to conventional PEG-mediated transfection of protoplasts. However, probably partially because of low entrapment of DNA, this system did not result in an effective increase in transfection efficiency over the conventional transfection procedure. A more effective use of liposomes for stimulating transfection was provided by the discovery that supernatants obtained during the washing of DNA-free liposome preparations stimulated PEG-mediated transfection of protoplasts. This effect appeared to involve small (0.1- to 0.3-micrometer diameter) poorly sedimented liposomes. It was most effective (more than 100-fold stimulation) with positively charged liposome supernatants and high (about 50% [wt/vol]) PEG concentrations. Stimulation of transfection was also observed with cloning ligation mixtures containing phi C31 DNA as the vector. Transformation by plasmids (but not by chromosomal DNA fragments) was also significantly more efficient in these conditions than in conventional protoplast transformation.